1987
DOI: 10.1073/pnas.84.15.5429
|View full text |Cite
|
Sign up to set email alerts
|

3'-orf and sor genes of human immunodeficiency virus: in vitro transcription-translation and immunoreactive domains.

Abstract: An in vitro transcription and translation procedure was designed to translate multiple open reading frames from cloned DNAs. For human immunodeficiency virus (HIV) cloned DNA carrying three open reading frames (sor, tat, and 3'-orf), the approach yielded three authentic polypeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Franchini et al (1987) reported similar results but found a slight increase of antibodies against vif with progression to AIDS. Ranki et al (1987) describe the presence of antibodies against vif in early HIV infection; similarily, Arya (1987) found in a limited amount of sera vif antibodies less frequently in AIDS patients than in healthy HIV carriers. This divergence may partially be explained by the fact that the recombinant vif protein used in our study represented the complete amino acid sequence of vif and that the proviral vif DNA was obtained from a different HIV clone than in some of the above-mentioned reports.…”
Section: Resultsmentioning
confidence: 99%
“…Franchini et al (1987) reported similar results but found a slight increase of antibodies against vif with progression to AIDS. Ranki et al (1987) describe the presence of antibodies against vif in early HIV infection; similarily, Arya (1987) found in a limited amount of sera vif antibodies less frequently in AIDS patients than in healthy HIV carriers. This divergence may partially be explained by the fact that the recombinant vif protein used in our study represented the complete amino acid sequence of vif and that the proviral vif DNA was obtained from a different HIV clone than in some of the above-mentioned reports.…”
Section: Resultsmentioning
confidence: 99%
“…The infectivity factor of human immunodeficiency virus type 1 (HIV-1), Vif, is a 23-kDa protein which modulates HIV-1 infection in cultured T-cell lines in a host celldependent manner (9,16,20,22,29,36,37) and is essential for infection of peripheral blood lymphocytes (1,7,9). Conservation of the vif open reading frame among many animal lentiviruses (23,38) and Vif immunogenicity in HIV-1-infected individuals (2,14,18,32) suggest that Vif is important in natural HIV-1 infection. Vif is both synthesized and active at a late phase of the viral life cycle (10,12,17,33), but it has no detectable effects on viral transcription or translation or virus secretion (1,7,16,20,36).…”
mentioning
confidence: 99%
“…As with other retroviruses, full-length RNA is translated into the gag core structural proteins and also, by a translational frameshift, the pol products (12), while the env mRNA is generated by a single splicing event. There are also a number of smaller, multiply spliced transcripts present in HIV-1-infected cells which code for some of the other genes of HIV-1, including the regulatory genes tat, rev, and nef (1,2,16). These transcripts consist of three or more exons, and their expression and that of the gag-pol and env mRNAs are differentially regulated.…”
mentioning
confidence: 99%